Analisis Konten Higher Order Thinking Skills (HOTS) dalam Buku Teks Tematik Siswa Kelas V Tema 1 - Tasya Andrawana; Siti Halidjah; Suparjan Suparjan (PALAPA, 2022)
This study aims to identify the content of Higher Order Thinking Skills (HOTS) in the thematic textbook for class V theme 1 especially sub-theme 1 and sub-theme 2. This study applied a qualitative descriptive approach with content analysis method. The data analysis technique used was Miles and Huberman model which included four stages, namely data collection, data reduction, data display, and drawing conclusion. The results reveal that the details of HOTS content in the thematic textbook for class V theme 1 particularly sub-theme 1 and sub-theme 2 consist of a combination of knowledge dimension and cognitive process dimension, particularly the knowledge dimension of cognitive process of level 4 (analyzing/C4) which comprises conceptual and metacognitive knowledge dimension. The details of HOTS content of knowledge dimension of level 5 (evaluating/C5) consist of conceptual and procedural knowledge dimension and metacognitive knowledge dimension, meanwhile the knowledge dimension of level 6 (creating/C6) encompasses procedural and metacognitive knowledge dimension. The number of HOTS content comprises the cognitive process dimension of level 4 (analyzing/C4) 27,78%, level 5 (evaluating/C5) 38,89%, and level 6 (creating/C6) 33,33%.